1997
DOI: 10.1126/science.276.5321.2034
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Regulation by S -Nitrosohemoglobin in the Physiological Oxygen Gradient

Abstract: The binding of oxygen to heme irons in hemoglobin promotes the binding of nitric oxide (NO) to cysteine␤93, forming S-nitrosohemoglobin. Deoxygenation is accompanied by an allosteric transition in S-nitrosohemoglobin [from the R (oxygenated) to the T (deoxygenated) structure] that releases the NO group. S-nitrosohemoglobin contracts blood vessels and decreases cerebral perfusion in the R structure and relaxes vessels to improve blood flow in the T structure. By thus sensing the physiological oxygen gradient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
783
2
19

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,028 publications
(837 citation statements)
references
References 15 publications
33
783
2
19
Order By: Relevance
“…Our data further show that the CBF response does not depend on deoxygenation of hemoglobin, which has been proposed as part of a universal mechanism for coupling of oxygen demand and supply. 65 Oxygen conc. of arterial blood 9,000 nmoL/mL Glucose conc.…”
Section: Differences Of Oxygen and Glucose Supplymentioning
confidence: 99%
“…Our data further show that the CBF response does not depend on deoxygenation of hemoglobin, which has been proposed as part of a universal mechanism for coupling of oxygen demand and supply. 65 Oxygen conc. of arterial blood 9,000 nmoL/mL Glucose conc.…”
Section: Differences Of Oxygen and Glucose Supplymentioning
confidence: 99%
“…92 Although the mechanisms are disputed, NO may have profound effects on tissue perfusion through interactions with hemoglobin. 93 Evidence suggests that S-nitroso-hemoglobin (SNO-Hb) may be an important and regulated source of intravascular NO. 93 In addition, stable NO metabolites (nitrate-NO 3 -and nitrite-NO 2 -) may provide an additional source of biologically active NO in hypoxic vascular beds 94 (Figures 5, 6).…”
Section: Potential Sources Of Vascular No During Hemodilutionmentioning
confidence: 99%
“…93 Evidence suggests that S-nitroso-hemoglobin (SNO-Hb) may be an important and regulated source of intravascular NO. 93 In addition, stable NO metabolites (nitrate-NO 3 -and nitrite-NO 2 -) may provide an additional source of biologically active NO in hypoxic vascular beds 94 (Figures 5, 6). In an experimental model of acute hemodilutional anemia, we have observed that whole blood methemoglobin (MetHb) levels are increased consistently by approximately 1-2%.…”
Section: Potential Sources Of Vascular No During Hemodilutionmentioning
confidence: 99%
“…It is therefore necessary to preserve NO bioactivity in the proximity of a pool of hemoglobin (∼10 mM) in the lumen. Several solutions to this paradox have been proposed, including i) the diffusion and transport limitation arises from the encapsulation of hemoglobin (Hb) in erythrocyte [8,9,10,11,12,13,14,5,15,16,17,18], ii) the formation of S-nitroso-hemoglobin (SNO-Hb) from the intramolecular transfer of nitrosylhemoglobin (HbFe II NO) [19,20,21,22,23,24,5,25], and iii) the NO bioactivity transduced from nitrite [26,27,28,29]. In the latter two cases, the formation of HbFe II NO can be argued to play a role for preserving NO bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…In early works, it has been suggested that the formation of metHbFe III from HbFe II NO is a direct reaction of O 2 with the bound NO. Stamler and coworkers utilized this idea of autooxidation reaction to describe denitrosylation [21]. However, later works began to consider that the autooxidation reaction may occur via three steps [36,37]: (1) the slow dissociation of NO from the iron center of hemoglobin or myoglobin, (2) the binding of oxygen to the newly formed deoxy-Fe II globin, and (3) the irreversible oxidation of HbFe II O 2 by NO referred to as NO dioxygenation (NOD).…”
Section: Introductionmentioning
confidence: 99%